Pengaruh aktivitas makro sosial dan Aktivitas mikrososial terhadap Sistim Multi Level Syari’ah Financing (MLSF) dan dampaknya terhadap minat investasi jama’ah pada PT. Rijan Dinamis Selaras (RDS) Pacet Mojokerto - Fikri Zainun Nasihin (FADZAT: Jurnal Ekonomi Syariah, 2020)
This study aims: 1) To analyze the effect of macro social activities on the Multi Level Syari'ah Financing System (MLSF). 2) To analyze the influence of micro-social activities on the Multi Level Syari'ah Financing System (MLSF). 3) To analyze the influence of macro-social activities on the investment interest of the congregation. 4) Analyzing the influence of micro-social activities on the investment interest of the jama'ah. 5) Analyzing the effect of the Multi Level Syari'ah Financing System (MLSF) on the investment interest of the congregation. 6) Analyzing the influence of social macro activities on the interest in investing in congregations with the mediation variable of the Multi Level Syari'ah Financing System (MLSF). 7) Analyzing the influence of micro-social activities on the interest in investing in congregations with the mediation variable of the Multi Level Syari'ah Financing System (MLSF). This research is descriptive-exploratory with explorative, descriptive and explanatory designs. The population is the employees of PT. Rijan Dinamis Selaras (RDS) Pacet Mojokerto totaling 38 people. Sampling using census technique The data collection used was a questionnaire with a 5 point Likert scale measuring instrument. Methods of data analysis using SmartPLS v. Software. 3.3.7. Structural equation analysis (SEM). The results of this study conclude: 1) Social macro activities have a significant effect on the Multi Level Syari'ah Financing System (MLSF) 2) Microsocial activities have no effect on the Multi Level Syari'ah Financing System (MLSF) 3) Social macro activities have no effect on investment interest jama'ah 4) Micro-social activities have a significant effect on the investment interest of the congregation 5) The Multi Level Syari'ah Financing (MLSF) system has no effect on the investment interest of the congregation 6) Social macro activities have an indirect effect on the investment interest of the congregation through the Multi Level Syari'ah Financing System (MLSF) 7) Micro-social activities have an indirect effect on the investment interest of the congregation through the Multi Level Syari'ah Financing System (MLSF)